Firm-Specific Determinants of Liquidity in Nepalese Commercial Banks - Ghimire, Shiva Raj; Agrawal, Nirdosh Kumar (Journal of Development Review, 2025)
Purpose - This study examines the determinants influencing liquidity in Nepalese commercial banks. This study analyzes the impact of firm-specific variables on the liquidity of Nepalese commercial banks covering the period from 2010/11 to 2022/23. Design/Methodology/Approach - The study employs a judgmental sampling technique to pick six commercial banks from a total of twenty in Nepal: Nabil Bank Limited, Standard Chartered Bank Limited, Global IME Bank Limited, NIC Asia Bank Limited, Rastriya Banijya Bank Limited, and Agricultural Development Bank Limited. Using a descriptive, correlation, and explanatory research design to look into the connection between the liquidity ratio, which measures liquid assets compared to total assets, and key firm-specific variables such as capital adequacy ratio, total loan-to-total-assets ratio, interest rate margin, deposits, and non-performing loans. Also, used the generalized method of moments (GMM) estimation of dynamic panel data from six commercial banks (from 2010/11 to 2022/23) and analyzed data spanning 13 years to identify significant patterns. Findings - The findings reveal that the capital adequacy ratio, deposit ratio, and net interest margin positively and significantly influence liquidity. Conversely, the total loan-to-total assets ratio and non-performing loans exhibit a strong negative relationship with liquidity. Orginality/Value - This study contributes to the existing literature by offering new empirical evidence on firm-specific determinants of liquidity. It provides practical guidance for improving liquidity management in Nepalese commercial banks. The insights are crucial for designing robust banking policies and strategies to ensure financial stability and operational efficiency in the banking sector.